Vermicomposting for treating household organic solid waste, agricultural waste and sewage sludge - احمد, محمد; هيثم شاهين; جنان عثمان (Latakia University Journal -Engineering Sciences Series, 2024)
The current trend in the waste management and disposal field focuses on transforming waste into useful materials or energy using various recycling and reusing methods. Using composting methods on organic solid waste have reduced the amounts of solid biological waste significantly. Therefore, research efforts are being made to develop sustainable and efficient techniques to treat organic waste and sewage sludge. In the past decades, vermicomposting have become a popular technique to produce high-quality composts, higher in nutrients than traditional composts and chemical fertilizers. The aim of this research is to produce a safe and nutritious compost using the vermicomposting technique on organic solid household waste, agricultural waste, and sewage sludge. The studied worm species is the Eisenia Fetida, also known as the Red Wiggler worms. The obtained compost proved to be rich in nutrients and conforming to the Syrian standard specifications for organic fertilizers. The worm species demonstrated high efficiency in decaying organic waste transforming it into a stable material, rich in nutrients, which can be safely used as an alternative to chemical fertilizers to enhance the soil nutritional levels.